Implementation of Good Corporate Governance on the Performance of PT. Garuda Indonesia - Amelia Azura; Fairuz Firjatullah; Maylin Azzahra; Nilam Utami Aqillah; Juliana Nasution (Penerbit Jurnal Indonesia, 2022)
Good corporate governance is very important in a company. It is used to improve the company's business, to control and direct labor relations and can even increase the responsibilities of company managers. The implementation of GCG has been stated in Law no. 40 of 2007 concerning Limited Liability Companies and Law NO. 19 of 2003 concerning BUMN and Minister of BUMN Regulation Number PER 01/MBU/2011 concerning the Implementation of Good Corporate Governance. Like our research this time which raised the case of GCG implementation at PT. GARUDA INDONESIA. The research method used is a qualitative literature study, this study aims to determine whether the implementation of GCG in PT. GARUDA INDONESIA produces good performance or not in the company. And the results of this study convey that PT.GARUDA INDONESIA received a